Toward a new personalized psycho-social approach for the support of prostate cancer and their caregivers dyads: a pilot study - Cincidda, Clizia; Pizzoli, Silvia Francesca Maria; Oliveri, Serena; Guiddi, Paolo; Pravettoni, Gabriella (Frontiers in Medicine, 2024)
Introduction Prostate cancer patients (PCP) often struggle with a significant emotional, physical, and social burden during the care-flow pathway. Noteworthy, PCP should not be considered a standalone patient, but someone who is connected with a relevant social environment and that is usually supported by a beloved one, the caregiver. The involvement of the caregivers through the care pathway might bring significant benefits both on the psychological and the treatment and decision-making side. The present pilot study aimed at preliminarily assessing quantitatively the psychological impact of a prostate cancer diagnosis on the degree of agreement of PCPs and their caregivers on medical decisions, coping resources and psychological distress levels. Methods 16 PCP and their caregivers were enrolled in the study and fulfilled a battery of standardized questionnaires. Results Results showed low concordance in decision making styles and preferences in patients and their caregivers and that the dyads showed similar depression symptoms levels. Relevant features of the psychological needs of the analyzed dyads, such as need for information and support, also emerged. Conclusion On the basis of these preliminary results, guidelines for the construction of tailored brief psychological support interventions for PCP dyads are provided.